2021
DOI: 10.1111/jai.14186
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tryptophan supplementation on stress and aggression in Nile tilapia

Abstract: Nile tilapia farmers must deal with production challenges, such as increased aggressiveness and high stress levels, which potentially diminishes fish welfare. Tryptophan supplementation is a strategy to cope with such problems. However, data is scarce on how tryptophan affects the aggressiveness of this species and other aspects need to be understood on how it influences stress in fish. In this study, we investigate how a 1× (0.32%), 4×(1.28%) and 8× (2.56%) supplemented tryptophan diet affects aggressiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The authors suggested it is necessary to validate the methodology for each species before using mirror 67 . In this context, several studies with Nile tilapia used the mirror test and showed plausible results for comparing intraindividual aggression 7 , 63 , 69 71 . Therefore, although limitations on the method exist, we consider that our results are plausible and present evidence that CBD can decrease Nile tilapia’s aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors suggested it is necessary to validate the methodology for each species before using mirror 67 . In this context, several studies with Nile tilapia used the mirror test and showed plausible results for comparing intraindividual aggression 7 , 63 , 69 71 . Therefore, although limitations on the method exist, we consider that our results are plausible and present evidence that CBD can decrease Nile tilapia’s aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The Nile tilapia ( Oreochromis niloticus ) (Linnaeus, 1857) is an African cichlid reared worldwide for farming and research purposes 7 . Nile tilapia production has been growing exponentially in the last few years, and the species has become the third most farmed fish in the world, with global production reaching approximately 4407.2 tons in 2020 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-mutualistic species, serotonin also decreases aggressive interactions [40][41][42] . Nile tilapia males that were fed a diet enriched with tryptophan (a serotonin precursor) also showed decreased aggression 43 . Further, as serotonin pathways in fish and mammals are similar 29,44 , this system could be associated with the reduced aggression observed during TS in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan was a precursor for the synthesis of the neurotransmitter serotonin (5-hydroxytryptpamine, 5-TH), which plays an important role in stress mitigation [7]. In addition, some previous studies reported that tryptophan had a suppressive effect on aggressive behavior and cannibalism of some fish species through the 5-HT pathway [8][9][10][11][12][13]. Reducing intraspecific aggression and cannibalism was very important in fish rearing because it was associated with survival rate [14][15][16].…”
Section: Introductionmentioning
confidence: 99%